2024
DOI: 10.1021/acs.est.3c06177
|View full text |Cite
|
Sign up to set email alerts
|

Global Responses of Soil Carbon Dynamics to Microplastic Exposure: A Data Synthesis of Laboratory Studies

Yangzhou Xiang,
Matthias C. Rillig,
Josep Peñuelas
et al.

Abstract: Microplastics (MPs) contamination presents a significant global environmental challenge, with its potential to influence soil carbon (C) dynamics being a crucial aspect for understanding soil C changes and global C cycling. This meta-analysis synthesizes data from 110 peer-reviewed publications to elucidate the directional, magnitude, and driving effects of MPs exposure on soil C dynamics globally. We evaluated the impacts of MPs characteristics (including type, biodegradability, size, and concentration), soil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(2 citation statements)
references
References 71 publications
0
1
1
Order By: Relevance
“…Long-term systematic studies, especially under realistic field conditions, are required. We found that PE had no significant effect on SOC, whereas Xiang et al observed an increase in SOC after PE MP pollution; this difference might be related to differing experimental conditions. Although polyester enhanced the C and N content, the increased C/N ratio outweighs any positive effects of this pollutant on the nutrient status.…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…Long-term systematic studies, especially under realistic field conditions, are required. We found that PE had no significant effect on SOC, whereas Xiang et al observed an increase in SOC after PE MP pollution; this difference might be related to differing experimental conditions. Although polyester enhanced the C and N content, the increased C/N ratio outweighs any positive effects of this pollutant on the nutrient status.…”
Section: Discussioncontrasting
confidence: 86%
“…However, this data synthesis did not include organic N or any other soil nutrients. Similarly, another data synthesis compared impacts of various important factors (such as exposure time and initial soil conditions) on SOC but did not incorporate other soil nutrients . Thus, our data synthesis takes the lead in investigating effects of multiple factors, to relate mechanistic knowledge of MP pollution impacts to key factors mediating MP impacts on the soil C and N status.…”
Section: Discussionmentioning
confidence: 99%